Alliance with EPR Effect: Combined Strategies to Improve the EPR Effect in the Tumor Microenvironment - Park, Jooho; Choi, Yongwhan; Chang, Hyeyoun; Um, Wooram; Ryu, Ju Hee; Kwon, Ick Chan (IVYSPRING INT PUBL, 2019)
The use of nanomedicine for cancer treatment takes advantage of its preferential accumulation in tumors owing to the enhanced permeability and retention (EPR) effect. The development of cancer nanomedicine has promised highly effective treatment options unprecedented by standard therapeutics. However, the therapeutic efficacy of passively targeted nanomedicine is not always satisfactory because it is largely influenced by the heterogeneity of the intensity of the EPR effect exhibited within a tumor, at different stages of a tumor, and among individual tumors. In addition, limited data on EPR effectiveness in human hinders further clinical translation of nanomedicine. This unsatisfactory therapeutic outcome in mice and humans necessitates novel approaches to improve the EPR effect. This review focuses on current attempts at overcoming the limitations of traditional EPR-dependent nanomedicine by incorporating supplementary strategies, such as additional molecular targeting, physical alteration, or physiological remodeling of the tumor microenvironment. This review will provide valuable insight to researchers who seek to overcome the limitations of relying on the EPR effect alone in cancer nanomedicine and go "beyond the EPR effect".
Keywords: TARGETED PHOTODYNAMIC THERAPY; IN-VIVO; MACROMOLECULAR THERAPEUTICS; MAGNETIC NANOPARTICLES; CANCER NANOMEDICINE; DELIVERY; ANGIOGENESIS; CHEMOTHERAPY; GROWTH; MECHANISMS